Copper source determines chemistry and topography of implant coatings to optimally couple cellular responses and antibacterial activity - Cordeiro, Jairo M.; Nagay, Bruna E.; Dini, Caroline; Souza, João G.S.; Rangel, Elidiane C. [UNESP]; da Cruz, Nilson C. [UNESP]; Yang, Fang; van den Beucken, Jeroen J.J.P.; Barão, Valentim A.R. (Elsevier, 2021)
Implant-related infections at the early healing period are considered one of the main risk factors in implant failure. Designing coatings that control bacterial adhesion and have cell stimulatory behavior remains a challenging strategy for dental implants. Here, we used plasma electrolytic oxidation (PEO) to produce antimicrobial coatings on commercially pure titanium (cpTi) using bioactive elements (calcium and phosphorus) and different copper (Cu) sources: copper acetate (CuAc), copper sulfate (CuS), and copper oxide (CuO); coatings containing only Ca and P (CaP) served as controls. Cu sources drove differential physical and chemical surface features of PEO coatings, resulting in tailorable release kinetics with a sustained Cu ion release over 10 weeks. The antibacterial effects of Cu-containing coatings were roughness-dependent. CuAc coating exhibited optimal properties in terms of its hydrophilicity, pores density, and limited surface roughness, which provided the most robust antibacterial activity combined with appropriate responses of human primary stem cells and angiogenic cells. Our data indicate that Cu source selection largely determines the functionality of Cu-containing PEO coatings regarding their antibacterial efficacy and cytocompatibility.
Keywords: Biofilm; Biomimetic material; Dental implant; Microarc oxidation; Osseointegration; Titanium